Asthma in primary schools. Issue 6592 (25th July 1987) - Storr, J; Barrell, E; Lenney, W
Abstract : Seven schools in the Lewes area were visited to identify which children were using inhalational treatment for asthma. The attitudes of the parents and schools were assessed, as was the children's skill in using inhalers. Five per cent of all children were receiving inhalational treatment with bronchodilator drugs. On average they had missed seven school days in the past year. The opinions of the parents about treatment appeared to be determined by the severity of the child's asthma. Most schools coped well with giving bronchodilators, though there was no real understanding of the nature of the disease or treatment. Most children who had received pressurised inhalers could not use them satisfactorily.